Effective Teaching Learning In Marketing Management Studies - Nur Hayati (International Conference on Education and Language (ICEL), 2013)
This paper is concerned with the most widely –used teaching methods within the sphere of university education and more precisely in the area of marketing tuition. The authors analyse these teaching methods and their characteristics in two different ways : Jigsaw Type and Mind Mapping. The aim of this paper is to investigate the possible differences between methods. The study shows interesting results.